The micrographic programme at the University Of Malaya Library - Kuak, M.S.J. (University of Malaya Library, 1989)
Describes the various types and stages of the history of of the microfilming and microfiching programme at the University of Malaya Library as well as the various types of materials that have been microfilmed or microfiched as part of UML's preservation and document delivery service. The frequent break downs of antiquated equipment have been the major cause for the slow down in micrographic activity in the last few years. Stress the need to acquire the appropriate equipment in order to maintain the necessary level of performance.